Toward Mycobacterium tuberculosis Virulence Inhibition: Beyond Cell Wall - Maria S. Kotliarova; Mikhail S. Shumkov; Anna V. Goncharenko (Microorganisms)
Mycobacterium tuberculosis (Mtb) is one of the most successful bacterial pathogens in human history. Even in the antibiotic era, Mtb is widespread and causes millions of new cases of tuberculosis each year. The ability to disrupt the host’s innate and adaptive immunity, as well as natural persistence, complicates disease control. Tuberculosis traditional therapy involves the long-term use of several antibiotics. Treatment failures are often associated with the development of resistance to one or more drugs. The development of medicines that act on new targets will expand treatment options for tuberculosis caused by multidrug-resistant or extensively drug-resistant Mtb. Therefore, the development of drugs that target virulence factors is an attractive strategy. Such medicines do not have a direct bacteriostatic or bactericidal effect, but can disarm the pathogen so that the host immune system becomes able to eliminate it. Although cell wall-associated targets are being actively studied for anti-TB drug development, other virulence factors important for adaptation and host interaction are also worth comprehensive analysis. In this review, specific Mtb virulence factors (such as secreted phosphatases, regulatory systems, and the ESX-1 secretion system) are identified as promising targets for novel anti-virulence drug development. Additionally, models for the search of virulence inhibitors are discussed, such as virtual screening in silico, in vitro enzyme inhibition assay, the use of recombinant Mtb strains with reporter constructs, phenotypic analysis using in vitro cell infection models and specific environments.